Neosyringophilopsis, a new genus of the subfamily Syringophilinae (Acari: Syringophilidae) - Skoracki, Maciej; Sikora, Boúena (Zootaxa, 2005)
A new genus, Neosyringophilopsis is described. This new genus is closely related to Syringophilopsis Kethley and is distinguished by the presence of the following characters: the propodosomal shield is divided longitudinally, setae lG of legs IV are absent, epimeres I are not fused to epimeres II. This new genus includes five recognized species: N. troglodytis (Fritsch) comb. nov., N. aegithali (Bochkov et al.) comb. nov., N. phylloscopi (Bochkov et al.) comb. nov., N. garrulaxi (Bochkov et al.) comb. nov., N. locustellus (Skoracki) comb. nov., and one new species N. acanthizus sp. nov.